Macrophage, a potential targeted therapeutic immune cell for cardiomyopathy - Chen, Ganyi; Jiang, Hongwei; Yao, Yiwei; Tao, Zhonghao; Chen, Wen; Huang, Fuhua; Chen, Xin (Frontiers in Cell and Developmental Biology, 2022)
Cardiomyopathy is a major cause of heart failure, leading to systolic and diastolic dysfunction and promoting adverse cardiac remodeling. Macrophages, as key immune cells of the heart, play a crucial role in inflammation and fibrosis. Moreover, exogenous and cardiac resident macrophages are functionally and phenotypically different during cardiac injury. Although experimental evidence has shown that macrophage-targeted therapy is promising in cardiomyopathy, clinical translation remains challenging. In this article, the molecular mechanism of macrophages in cardiomyopathy has been discussed in detail based on existing literature. The issues and considerations of clinical treatment strategies for myocardial fibrosis has also been analyzed.